Transparency, Liquidity, and Valuation: International Evidence on When Transparency Matters Most - LANG, MARK; LINS, KARL V.; MAFFETT, MARK (Journal of Accounting Research, 2012)
ABSTRACT We examine the relation between firm‐level transparency, stock market liquidity, and valuation across countries, focusing on whether the relation varies with a firm's characteristics and economic environment. We document lower transaction costs and greater liquidity (as measured by lower bid‐ask spreads and fewer zero‐return days) for firms with greater transparency (as measured by less evidence of earnings management, better accounting standards, higher quality auditors, more analyst following, and more accurate analyst forecasts). The relation between transparency and liquidity is more pronounced in periods of high volatility, when investor protection, disclosure requirements, and media penetration are poor, and when ownership is more concentrated, suggesting that firm‐level transparency matters more when overall investor uncertainty is greater. Increased liquidity is associated with lower implied cost of capital and with higher valuation as measured by Tobin's Q . Finally, a mediation analysis suggests that liquidity is a significant channel through which transparency affects firm valuation and equity cost of capital.